Review of the monograph by Boris A. Shenderov, Alexander V. Sinitsa, Mikhail M. Zakharchenko, Christine Lang «Metabiotics. Present State, Challenges and Perspectives» (Springer Nature Switzeland AG, 2020) - A. N. Suvorov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2020)
.